2017
DOI: 10.4236/oalib.1103332
|View full text |Cite
|
Sign up to set email alerts
|

Giant Bladder Stone and Renal Failure: A Case Report, Literature Review and Future Perspectives

Abstract: We present a male patient, 52 years old, with acute renal failure due to giant bladder stone. In first presentation with acute renal failure, tomography has shown a bladder stone with 10 cm in its largest diameter associated with bilateral ureterohydronephrosis. It was initially treated by bladder catheterization and indicated emergency dialysis and subsequently submitted to surgical treatment through open cistolitotomy. During the procedure it was possible to observe the giant calculus, adhered to the trigone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…11 Diniz et al who performed the literature review on giant bladder stone and renal failure a few years later, concluded that bladder stone greater than 400 grams may be associated with renal failure. 12 On the other hand, a handful of other reported cases with heavier (>1000 gm) and bigger bladder stones (>10 cm) have normal collecting systems and normal renal function. [13][14][15][16] The giant bladder stone in our case weighed 810 grams and measured 12×10 cm.…”
Section: Discussionmentioning
confidence: 98%
“…11 Diniz et al who performed the literature review on giant bladder stone and renal failure a few years later, concluded that bladder stone greater than 400 grams may be associated with renal failure. 12 On the other hand, a handful of other reported cases with heavier (>1000 gm) and bigger bladder stones (>10 cm) have normal collecting systems and normal renal function. [13][14][15][16] The giant bladder stone in our case weighed 810 grams and measured 12×10 cm.…”
Section: Discussionmentioning
confidence: 98%
“…Diniz et al [5] reported two cases of women with giant vesical calculus causing renal failure. This review study also concluded that boys are 8 times more affected than girls, and the most commonly presented at the age of 2-5 years, while renal insufficiency due to giant vesical calculus reported in three male children.…”
Section: Discussionmentioning
confidence: 99%